Change Leadership in The Development of Digital Learning Ecosystem: A Case Study at Brawijaya Smart High School - Nur Arifah; Ibrahim Bafadal; Raden Bambang Sumarsono (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
Digital-based education has become one of the important elements to enhance the quality of learning in various educational institutions, especially in senior high schools. Brawijaya Smart High School Indonesia (BSS) is the subject of this study. The purpose of this study is to describe how the leaders of BSS are leading the change towards a digital learning ecosystem. The research method involves data collection through interviews, observations, and document analysis related to digital change initiatives in the school. The findings of this study reflect how leaders at BSS play a key role in designing, implementing, monitoring, and evaluating the implementation of digital education transformation. This in-depth study explores the motivators, enablers, and inhibitors of transformational leadership and the impact of change on the school's learning ecosystem. In addition, the leaders ensure that integrating digital-based technologies into the curriculum is effective, improves the quality of learning, and meets the expectations of learners and stakeholders. A qualitative approach with a case study design was used to uncover the facts in the field. Data analysis took place in three simultaneous stages, namely data reduction, data presentation, and conclusion (verification) while triangulating sources carried out data validity until the researcher found the desired certainty. This research provides an in-depth insight into how change leadership in developing digital-based learning ecosystems in BSS can positively contribute to modern education's development. The implications of this research can also help other schools to identify the best practices and develop effective leadership strategies in this current era.